Optimización del servicio de mantenimiento en el Hospital Dr. Maximiliano Peralta Jiménez - Vargas-Quirós, Tatiana María (Instituto Tecnológico de Costa Rica, 2017)
The present project was developed at the Dr. Maximiliano Peralta Jiménez Hospital, a public institution that belongs to the Costarrican Institution for Social Welfare (CCSS for its Spanish acronym), the project provides tools to optimize the current maintenance service. Initially, it is made a reference of the general information of the institution, the current situation, and the objectives to develop in the project, as well as the extents and limitations of the preparation of the project. In order to learn the maturing of the maintenance, the engineering and maintenance service of the Hospital, is evaluated by the COVENIN 2500 norm, which makes possible to define opportunities for the improvement of the department. It’s demonstrated that there is an absence of a standardized maintenance management processes. It is for this reason that a Maintenance Management Model is proposed, which allows to integrate, and guide the subareas of the department. The implementation process is done through a strategy that involves all hierarchical levels, in order to improve customer’s satisfaction, and optimize the scheduled maintenance process. Using the methodology called “Balanced Scorecard”, is optimized the current scorecard, what allows to measure the maintenance management in four perspectives, at the same time, the goals to be achieved are defined, as part of the control and continuous improvement process. Besides, a strategic map is designed, according to the maintenance service characteristics. As part of the implementation process, strategies are designed, and potential risks analyzed, due to implementation of the proposed changes, though this analysis it is determined the procedure to be applied, in order to mitigate risk.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Evaluación; Mantenimiento; Gestión de mantenimiento; Criticidad de equipos; Balanced scorecard